Use of n-actylcisteine in the prevention of induced nephropathy for a contrast in rats - Inci, M. F.; Salk, I.; Solak, O.; Vurdem, U. E.; Inci, R. (Ene Ediciones Sl, 2012)
Objective: To date, there is no effective treatment of contrast induced nephropathy (CIN). N-acetylcysteine (NAC) has yielded some promising results recently in the prevention of CIN. In this study, the structural effects of NAC on CIN were analyzed. Material and methods: Fourty adult Wistar albino male rats were randomly allocated to four groups. The first group was the control group (n=9) which received only distilled water; second group was the contrast group (n = 10) which received CM; the third group was the contrast plus NAC group (n = 8) which received CM and was treated with NAC; and the last group was NAC group (n = 10) which received only NAC. At the end of the 3rd day, the right and left kidneys were removed and reserved for histopathological examination. All tissue sections were examined with light microscope looking for histopathological changes by the same experienced renal pathologist, without knowledge of the prior treatment. Histopathological examination was conducted in a blinded fashion, and glomerular injury scores, arteriolar injury scores and tubulointerstitial injury scores were calculated. Results: There was a significant difference among the scores of glomerular injury, arteriolar injury and tubulointerstitial injury in all groups (p <0.05). The scores of glomerular, arteriolar and tubulointerstitial injury of the group-1 and group-4 were not significantly different from each other (p <0.05). Renal injury scores in group-3 group were higher than in group-1 and-4, but significantly lower than the scores of the Group-2 (p <0.05). Conclusion: NAC could be useful to prevent the renal tissue from CIN, especially in high-risk patients. (C) 2011 AEU. Published by Elsevier Espana, S.L. All rights reserved.
Uso de n-acetilcisteína para la prevención de la nefropatía inducida por contraste en ratas
Keywords: N-acetylcysteine; Contrast medium; Contrast induced nephropathy; Nephrotoxicity